Assessing sexual and reproductive health dimensions tools in women with type 1 diabetes mellitus with regard to Consensus-based Standards for the selection of health status Measurement Instruments checklist - Azimi, Nasrin (J Educ Health Promot, 2020)
A valid tool is of paramount importance in determining women's sexual and reproductive health status, meeting their health needs, and recognizing the effectiveness of some interventions. This review study aimed to assess sexual and reproductive health dimensions tools in women with type 1 diabetes mellitus with regard to Consensus-based Standards for the selection of health status Measurement Instruments (COSMIN) checklist. In this review study, in addition to Iranian databases (MagIran, Sid, Irandoc), non-Iranian databases (PubMed, Scopus, Embase, and Web of Science) and Google Scholar search engine were considered. The mentioned databases were searched for articles in English and Persian published within 2000–2019, using the search strategy for each database and Boolean operators along with appropriate keywords according to the MESH term. Articles with nonresearcher-made tools measuring the sexual and reproductive health concepts and dimensions were included in the present study. Afterward, the psychometric properties of the tools were assessed according to the COSMIN checklist. In the selected articles, there were 14 psychometrically valid tools to be assessed from 151 articles containing the sexual and reproductive health dimensions; among which, seven tools were evaluated with regard to COSMIN. None of the tools also had all the features noted in COSMIN. Moreover, all the concerned scales were not interpretable and accountable; however, a majority of them had internal consistency and construct validity. In this study, there was no valid and specific tool for measuring sexual-reproductive health status in this population group. Therefore, it is necessary to develop a valid tool according to the dimensions and needs of specific reproductive health in type 1 diabetes.